Layer-dependent quantum cooperation of electron and hole states in the anomalous semimetal WTe2 - Pranab Kumar Das (Nature Portfolio, 2016)
Tungsten ditelluride is a semi-metallic two-dimensional material that has exhibited large magnetoresistance. Here, the authors use angle- and spin-resolved photoemission spectroscopy to investigate the band structure of this transition metal dichalcogenide and identify layer-dependent electronic behaviour.